PENGARUH LIKUIDITAS, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Pipin Sri Sudewi; Rosalina Anindya Kartika; Sri Hartati (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
This study aims to examine the effect of liquidity, profitability and dividend policy on stock prices with firm size as the moderating variable. The population in this study is the annual report of all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period, namely 154 manufacturing companies listed on The Indonesia Stock Exchange. The results of the regression analysis is: Y = 9.589 + 1.243 Ln NPM – 0.395 LnNPM*Size – 0.471 Lb CR. The regression coefficient value of Ln NPM is 1.243, meaning that every one percent increase in profitability will affect the stock price increase of 1.243 percent. With a t value of 8,246 and sig. 0.000, meaning that profitability has a significant positive effect on stock prices. The regression coefficient value of the Ln NPM*Size variable is -0.395. With the value of t count -4,423 with sig. 0.000, meaning that the interaction between profitability and firm size has a negative effect on stock prices. The value of the Ln CR regression coefficient is -0.471, meaning that every one percent increase in liquidity will affect the stock price decline of 0.471 percent. The value of t count is -3.957 and sig. 0.000, meaning that profitability has a significant negative effect on stock prices.